Safety and Efficacy of Achilles Tenotomy under Local Anaesthesia: as Part of the Ponseti Clubfoot Management -Experience at the Sudan clubfoot clinic - Shaheen, Samir; Abdalla, Musaab Mohamed (Gezira Journal of Health Sciences; Vol 11 No 2 (2015), 2015)
Introduction: Ponseti method of treatment of clubfoot is a gold standard method. It includes serial casting to be followed by percutaneous tenotomy of the Achilles tendon under local anaesthesia. In the current study the safety and efficacy of tenotomy under local anaesthesia following serial casting will be studied. Patients and Methods: 89 patients who were seen at the Sudan Clubfoot clinic at Soba University Hospital between 2011 and 2012. All underwent serial casting according to Ponseti method and that was followed by Achilles tenotomy under local anaesthesia using a single stab using a size 15 scalpel. Results: there were 89 patients (135 feet), 64 [71.9%] males and 25 (28.1%) females. 46 patients (51.1%) had bilateral involvement. Familial history was there in 11 (11.2%) babies.  Tenotomy was performed in all feet after an average of 6.2 casts (range, 3 to 11). All were discharged 2 hours after the tenotomy. No adverse events were related to local anaesthesia and/or the procedure itself, and there was no delay in discharge in any of the operated babies.  All patients had an uneventful course. Only one patient (1.12%) had previous conservative treatment before coming to the clinic. Pressure sores were observed as a result of casting in one foot. Residual equinus deformity after the tenotomy was experienced in 5 feet. 86 of the parents were satisfied with the correction. The rest; 3 patients (3.37%) were not satisfied because of the residual equinus. Conclusion: Tenotomy procedure using local anaesthesia is an effective and safe procedure.